Measuring Agricultural Means of Influence on Young Adults via Instagram in the United States - Samantha Bennett; David S Martin; Jason T. Sawyer; Soren P. Rodning; Don Mulvaney (Journal of Applied Communications, 2024)
Notable differences have been observed in how society perceives and understands the agricultural industry. Consumers today are concerned with how their food is raised and produced, and drastic changes in how information is gathered regarding those subjects have occurred due to the rapid development of digital media. As a result, the agricultural industry has fallen behind in ensuring accurate information is shared about the daily work done to feed the world. A form of digital media that has infiltrated the daily lives of society is social media (SM). This study sought to evaluate the impact established agricultural social media influencers (SMIs) on Instagram can have on changing participants' perceived knowledge regarding several agricultural topics. Participants were recruited through the platform Prolific and were asked to complete an anonymous Qualtrics survey. Survey questions were asked before and after participants were shown example images of agricultural SMIs. Data collected were analyzed utilizing IBM SPSS (Version 28) to compare pre-image and post-image results to determine the contents' impact on participants' perceived knowledge of subjects relating to agriculture. Results indicated significant differences between the pre-image and post-image perceived knowledge results and between different forms of reported engagement willingness.
Keywords: Agriculture Communications; Digital Media; Instagram; Social Media Influencer; Young Adults